Information Literacy: A Study Applied in a Primary School - S.Serap Kurbanoğlu; Buket Akkoyunlu (Türk Kütüphaneciliği)
An information society needs individuals who have lifelong learning skills. Information literacy, the ability to find and use information, is the keystone of lifelong learning. Therefore, teaching information literacy skills to students and integrating it into the school curriculum have a great importance. In this paper, plan- ning and pilot study steps of an applied study to teach information literacy skills in a primary school to 6th grade students and the fındings of the pilot study are introduced.